The impact of the expansion of the Bolsa Família programme on the time allocation of youths and labour supply of adults - Lia Chitolina; Miguel Nathan Foguel; Naercio Menezes-Filho (International Policy Centre for Inclusive Growth (IPC-IG), 2013)
This paper evaluates the impact of the 2007 expansion of the Bolsa Família programme to families with youths aged 16 to 17 years (Benefício Variável Jovem) on the time allocation of youths and on the labour supply of adults. The differences-in-difference estimator was used to compare households among the poorest 20 per cent with youths of 16 years of age with households in the same income bracket with youths of 15 years of age. The results show that granting the benefit had a significant and positive impact on school attendance and on the decision of young people to study and work at the same time. The effects on school attendance were stronger for males and when the child was the youngest in the household. With respect to the labour supply of parents, a positive impact was found on the mothers' probability of employment.
Keywords: D13; I38; J22; 330; Bolsa Família Programme; Impact Assessment; Differences-in-Difference